Toxic and mutagenic effect of biologically active substances from Inula britannica L. (family Compositae) (Experimental biology, 2018)
Biologically active substances (BAS) from the shoot and root parts of Inula britannica L.  (Compositae family) have been obtained. Purity indicators (moisture, total ash); indicators of extractive substances, amino acid and fatty acid compositions have been determined. The main groups of biologically active substances were identified using one- and two dimensional paper chromatography, thin layer chromatography on fixed layer of sorbent. Comparative analysis of the quantitative content of BAS from the shoot and root parts of the Inula britannica showed that the root part is dominated by saponins, tanning substances, polysaccharides, flavonoids, and B2 and C vitamins, and the shoot part is dominated by amino- and organic acids. As a result of the extraction of the shoot and root parts of Inula britannica followed by freeze-drying contingent phytoproducts consisting of BAS were obtained and tested for toxic and mutagenic activity. Toxic and mutagenic effects of BAS from the shoot and root parts of I. britannica have been studied using barley seed germination test and chromosome aberration assay of the germ cells from the root tip of barley. It is found that the BAS in the studied concentrations (25.0, 50.0 and 100.0 mg/l) had no phytotoxic and mutagenic action. The barley seeds treated with aqueous solutions of elecampane extracts at all concentrations had shown no reduction in germination as compared with control plants. Germination of seeds treated with aqueous solutions of methyl methanesulfonate (MMS, classical mutagen) at concentrations of 5.0 mg / L was 74.33%. Comparative analysis showed that the germination of seeds treated with the concentrations of MMS fell 1,26 (p
Keywords: biologically active substances, mutagen, seed germination, chromosome aberrations, Inula britannica.